2014
DOI: 10.1071/rd13259
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian fertility preservation through cryobiology: value of classical comparative studies and the need for new preservation options

Abstract: Human-related fertility preservation strategies have enormous potential for helping sustain and protect other species, especially to assist managing or ‘rescuing’ the genomes of genetically valuable individuals, including endangered species. However, wider-scale applications are limited by significant physiological variations among species, as well as a lack of fundamental knowledge of basic reproductive traits and cryosensitivity. Systematic and comparative cryopreservation studies (e.g. on membrane biophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“… 50 However, there appear to be significant species variance in tissue cryosensitivity. For example, we have found that felid testicular tissue survives vitrification better than the same tissue treated the same way from laboratory rodents (based on both structural and functional assays 13 ). Interestingly, testicular tissues from ungulates (deer, gazelles, and antelopes) appear to survive slow freezing better than vitrification.…”
Section: New Advances In Male Fertility Preservation Applicable To Wimentioning
confidence: 98%
See 3 more Smart Citations
“… 50 However, there appear to be significant species variance in tissue cryosensitivity. For example, we have found that felid testicular tissue survives vitrification better than the same tissue treated the same way from laboratory rodents (based on both structural and functional assays 13 ). Interestingly, testicular tissues from ungulates (deer, gazelles, and antelopes) appear to survive slow freezing better than vitrification.…”
Section: New Advances In Male Fertility Preservation Applicable To Wimentioning
confidence: 98%
“…There also are many examples of “milestone” births using frozen–thawed spermatozoa 11 12 with the incidence of success completely dependent on having an excellent understanding of the female reproductive physiology in the target species. 4 13 …”
Section: The Critical Roles Of Reproductive Sciences and Genome Resoumentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to fertility preservation for women, ovarian tissue cryopreservation can be used for conservation of wildlife species through gamete rescue (Comizzoli & Wildt, ). Ovarian tissue cryopreservation by slow freezing has been successfully performed in the domestic cat (Tanpradit, Comizzoli, Srisuwatanasagul, & Chatdarong, ) and in lions (Wiedemann et al., ), while ovarian tissue vitrification has yielded less successful results in the domestic cat (Luvoni et al., ; Tanpradit et al., ).…”
Section: Introductionmentioning
confidence: 99%